PENERAPAN METODE ROLE PLAY UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB PESERTA DIDIK KELAS V DI SD IT TUNAS INSAN CENDEKIA - Afifah Ardya Pusparani; Syaripudin Basyar; Ahmad Iqbal Hasan; Koderi (CV. Lafadz Jaya, 2026)
This study was motivated by the low level of Arabic speaking skills (maharah kalam) among Year 5 pupils at SD IT Tunas Insan Cendekia, characterised by a lack of confidence in speaking, limited vocabulary, and poor learning outcomes. The aim of this study was to examine the application of the role-play method in Arabic language teaching and to assess the improvement in pupils’ speaking skills following the implementation of this method. This study employed a Classroom Action Research (CAR) design using both qualitative and quantitative approaches, conducted over two cycles. Data collection techniques included observation, interviews, oral tests, and documentation. The results of the study indicate that students’ speaking skills improved in each cycle, as evidenced by the average score rising from 69 in the pre-cycle stage to 74.1 in Cycle I, and further increasing to 85.3 in Cycle II, with a mastery rate of 88%. Furthermore, the students appeared more active, confident, and bold in practising Arabic dialogue. Thus, the application of the role-play method proved effective in improving students’ Arabic speaking skills.